Teacher expectations and student literacy engagement and achievement. (14th March 2016) - Pantaleo, Sylvia
Abstract: Notwithstanding the complex and dynamic nature of teaching and learning in schools, over four decades of research findings have consistently revealed a correlation between teacher expectations and student achievement. Focusing on teacher expectations for the narrative structures created by young children, this article features a discussion of data gathered during a multifaceted study with 7‐ and 8‐year‐old students. The overall purpose of the case study research was to explore the development of student understanding of elements of visual art and design and diverse narrative structures in picturebooks. For the culminating activity of the research, the students had opportunities to apply and transform their knowledge of the instructional foci when they composed their own multimodal print texts. Analysis of the students' narrative structures revealed the multiple forms of metalepsis, the purposeful breaking of storyworld/narrative boundaries, evident in their writing and artwork. In addition to a discussion about the socially situated nature of the children's multimodal text‐making, the article includes a consideration of the importance of teacher expectations with respect to student literacy engagement and achievement.